ANALISA TINGKAT PENERIMAAN APLIKASI SCRATCH MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Gunadi, Goldie; Sudaryana, I Ketut (Infotech: Journal of Technology Information, 2021)
In connection with the need for making instructional media applications by teachers in the distance learning process, PT. Bangun Satya Wacana (BSW) through the Diginusa department held training on the use of the Scratch visual programming application to create learning materials such as games, animations and interactive quizzes. Scratch is a graphical programming language using drag and drop command blocks. Besides that, Scratch can be used both online and offline, so it is very helpful for the distance learning process (DLP). This research aims to see how the level of acceptance of teachers to Scratch using the Technology Acceptance Model (TAM) method. The indicators measured are Self-Efficacy, Complexity, Perceived Usefulness, Perceived Ease of Use, Intention to Use and Actual Technology Use, then analyzed by linear regression method with the help of IBM SPSS software. From the results of the analysis carried out, it can be seen that the Intention to Use affects the Actual Technology Use. Perceived Usefulness and Perceived Ease of Use together affect the Intention to Use. Perceived Ease of Use, Self-Efficacy and Complexity together have a significant effect on Perceived Usefulness.